Effect of preformed immune complexes on the clearance and tissue localization of single-stranded DNA in mice. - Emlen, W (1980)
Recent studies have shown that DNA is cleared from the circulation extremely rapidly by the liver, and that normal individuals have low or immeasurable levels of circulating DNA. In some patients with SLE and in NZB/W mice, however, significant amounts of free DNA as well as DNA-anti-DNA immune complexes have been found in the circulation, suggesting a possible defect in DNA clearance in these conditions. To delineate factors which might contribute to the persistence of DNA in the circulation, we have assessed the effects of immune complexes on the clearance of single stranded DNA in normal C57Bl/6J mice. HSA-anti-HSA immune complexes at five-fold antigen excess were injected intravenously and after a variable, the clearance of single-stranded DNA was determined. Clearance of all doses of DNA was markedly suppressed 6 to 12 hr after the administration of immune complexes and returned to normal by 24 hr. Immune complexes decreased DNA clearance by blocking the hepatic uptake of DNA without altering the distribution of DNA to other organs. Histology and studies on the effect of immune complexes on the clearance of bromosulphophthalein (BSP) and sulphur colloid suggest that immune complexes affect DNA clearance by altering hepatic blood flow. The results obtained in this study suggest that circulating immune complexes in patients with SLE or in other conditions may suppress normal DNA clearance, and thereby contribute to the persistence of DNA in the circulation.